Gold extraction using alternatives to cyanide: Ultrasonic reinforcement and its leaching kinetics. (January 2023) - Gui, Qihao; Fu, Likang; Hu, Yuting; Di, Haokai; Liang, Ming; Wang, Shixing; Zhang, Libo
Highlight: The synergistic pretreatment of ozone and ultrasound was developed for refractory gold ore. The pretreatment effectively oxidized sulfide enclosure and inhibits the secondary enclosure. The Au and Ag leaching rates were 93.52 % and 61.25 %, respectively. Abstract: A novel eco-friendly synthetic gold lixiviant (Jinchan) was used to recover gold from gold ores. Ultrasound was used to improve gold leaching efficiency and recovery percentage. The differences between ultrasonic and conventional leaching were investigated by comparing the effects of temperature, ultrasonic power, pH variation, and Jinchan concentration on gold leaching. The gold leaching percentage could be effectively increased from 42.21 % to 94.72 % using ultrasound, and the gold leaching time could be reduced. Kinetic studies indicated that Jinchan leaching was primarily controlled by internal diffusion. The apparent activation energy could be effectively reduced from 30.12 kJ/mol to 23.07 kJ/mol under ultrasound reinforcement. The reaction rate constant (k) of leaching was significantly improved by ultrasound.